Perceived concern about the new strain of the influenza and obtaining the vaccine in China, Japan and South Korea. Issue 3 (May 2017) - Kamimura, Akiko; Armenta, Bianca A.; Nourian, Maziar M.; Wright, Lindsey; Rathi, Naveen; Chernenko, Alla
Abstract: This study compares the factors, which influence individuals from the countries of China, Japan and South Korea to obtain any type of influenza vaccines and their perceived concerns about the new strain of the influenza - pandemic (H1N1) 2009. The data analyzed was from the East Asian Social Survey (EASS), Cross-National Survey Data Sets: Health and Society in East Asia, 2010 (ICPSR 34608) ( N = 7938). The results of this study suggest that individuals who are concerned about the new strain of influenza are more likely to have obtained influenza vaccine. In these countries, perceived concerns may be directly related to vaccine-related behaviors. The results of this study also indicate that there are variations within each country regarding as to why individuals do or do not obtain the influenza vaccine. Over all, this project provides new insights about the acquisition of the influenza vaccine within China, Japan and South Korea, which will be useful for medical practice within these countries and future research.